PLANO DE AÇÃO COMO INSTRUMENTO DE ANÁLISE DAS REPRESENTAÇÕES SOCIAIS DOS ALUNOS DO CURSO ATENÇÃO BÁSICA EM SAÚDE – UNASUS/UFMA/PROVAB. - FERNANDES, Ana Carolina Uruçu Rego (2018)
Introduction- The present research is about a study about the students’ Social Representations from the Specialization Course in Basic Health Care of the Open University of SUS - UNASUS / UFMA, inserted in the Program of Valorization of Basic Care - PROVAB in the period of 2012 to 2014. Methodology- This study has a qualitative nature. Data collection was performed through the Monsys Pedagogical Monitoring System, registered by the National Industrial Production Institute - INPI under the number BR 51 2014 001542-4. The initial sample consisted of 764 Course Final Assignments – CFA. After exclusion of those with less than 3 descriptors, 719 studies were selected. In order to homogenize the data, the semantic organization of the key words of Course Final Assignment was carried out, categorizing these according to the Descriptors in Health Sciences - DHS. Of the 719 papers selected, a prototype analysis of 2,154 descriptors, here called evocations, resulted. Objective - To analyze the Social Representations through the students’ Course Final Assignments of the Specialization Course in Basic Health Care of UNASUS / UFMA, inserted in the Program of Valorization of the Professional of Basic Attention (PROVAB). Results -After prototype analysis performed through the Openevoc® 0.83 program it was verified that the mean frequency of evocations ranged from 2.14% - 8.87. In the general analysis of the States there was a higher recall frequency for Hypertension (6.55%), Oral Health (6.04%) and Pregnancy (5.66%). Conclusion - During the research, the consonance between the frequencies of evocations and the health indicators of the states studied was noted, indicating the correct pedagogical choice of UNASUS / UFMA to develop course completion papers in the format of action plans. This study suggests through the Social Representations of the students’ Course Final Assignments from the Basic Health Care Course that the most prevalent health problems in the areas studied are related to Hypertension, Oral Health and Pregnancy.